The Implementation of Performance Assessment Through Virtual Laboratory to College Students’ Creative Thinking Skills - Ratih Permana Sari; Mauliza Mauliza; Muhammad Nazar; Nahadi Nahadi (Postgraduate, University of Mataram, 2021)
Recent learning activity is tend to be implemented by guided experiment and there is an absence of further assessment. The aim of this study is to implement the performance assessment through the virtual laboratory to improve college students’ creative thinking skills. This quantitative descriptive research used quasi experimental research method with one shot case study research design. The sample of this research was the college students on academic year 2018/2019 which totally amount 27 students. The performance assessment data was collected by observation instrument which applied during the preparation, implementation, and the presentation of experiment result stages of virtual laboratory learning. The result of the study showed the implementation of assessment on the presentation of experiment result stage for the whole learning materials is higher than in the preparation and implementation stage with the average score of presentation of experiment result is 88.3%. The implementation of performance assessment through the virtual laboratory showed the improvement on each indicator in college students’ creative thinking skills. The highest score was the evaluation indicator with the value of 0.69. It can be concluded that the implementation of performance assessment through the virtual laboratory is able to improve college students’ creative thinking skills, especially at the evaluation indicator